2009
DOI: 10.1016/j.bmcl.2009.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship studies of small-molecule inhibitors of Wnt response

Abstract: Suppression of oncogenic Wnt-mediated signaling holds promise as an anti-cancer therapeutic strategy. We previously reported a novel class of small molecules (IWR-1/2, Inhibitors of Wnt Response) that antagonize Wnt signaling by stabilizing the Axin destruction complex. Herein, we present the results of structure/activity relationship studies of these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 11 publications
4
123
0
1
Order By: Relevance
“…While the Wnt inhibitor Dkk1 was down‐regulated, Wnt effector Tcf4 was increased by Lox inhibition (Figure S4). It has been previously demonstrated that IWR‐1‐endo, an inhibitor of Wnt pathway, induces Axin2 protein levels and promotes β‐catenin degradation by stabilizing Axin‐scaffolded destructive complexes 26. Here, we found that IWR‐1‐endo treatment decreased protein levels of β‐catenin and CHOP‐10 expression induced by Lox inhibition, while subsequently repressing osteogenesis with lower expression of Runx2 and Osterix, along with lower calcium deposition (Figure 3C,D).…”
Section: Resultsmentioning
confidence: 99%
“…While the Wnt inhibitor Dkk1 was down‐regulated, Wnt effector Tcf4 was increased by Lox inhibition (Figure S4). It has been previously demonstrated that IWR‐1‐endo, an inhibitor of Wnt pathway, induces Axin2 protein levels and promotes β‐catenin degradation by stabilizing Axin‐scaffolded destructive complexes 26. Here, we found that IWR‐1‐endo treatment decreased protein levels of β‐catenin and CHOP‐10 expression induced by Lox inhibition, while subsequently repressing osteogenesis with lower expression of Runx2 and Osterix, along with lower calcium deposition (Figure 3C,D).…”
Section: Resultsmentioning
confidence: 99%
“…In order to test this hypothesis, we performed in vivo treatments using cell permeable small molecule inhibitors of the Wnt/ b-catenin pathway, endo-IWR-1 25 and PNU-74654 26 . Endo-IWR-1 acts as a stabilizer of Axin, thereby stimulating the degradation of cytoplasmic b-catenin and constitutively inhibiting the Wnt/b-catenin pathway, without altering the pool of membrane tethered b-catenin 25,27 .…”
Section: Resultsmentioning
confidence: 99%
“…This molecule has been shown to reduce the amount of b-catenin and to inhibit the transcriptional response to Wnt/b-catenin signalling in developing zebrafish and Xenopus embryos and larvae 28,29 , indicating its suitability for in vivo studies. In order to confirm endo-IWR-1 phenotypes, we used PNU-74654 that prevents the interaction between b-catenin and the transcription factor TCF 26,30 . Treatment with either molecule from 33 to 55 hpf allowed us to avoid interferences with earlier global functions of b-catenin 31 , and to specifically target the period during which cell proliferation reorganizes around the ventral midline and massive neural differentiation occurs.…”
Section: Resultsmentioning
confidence: 99%
“…We used the Porcn inhibitor Wnt-C59 (C59) to reveal the role of Wnt secretion in the formation of distinct intra-and extracellular fractions of Wnt3EGFP. In parallel, IWR-1, another inhibitor of Wnt signaling acting at the level of β-catenin activity in target cells, and thus not influencing secretion, was used for in vivo comparison of inhibitor action Lu et al, 2009).…”
Section: Block Of Porcupine Affects Wnt3egfp Secretionmentioning
confidence: 99%